Preference exercises (weightlifting - Albulayomterc) in the development of the explosive capacity of men hostile to the muscles (100 m) free for youth - Naama, Wafaa (Journal of Physical Education, 2012)
The Centered research problem in that a lot of coaches to Aevdilon diversity in exercises to develop physical abilities and their dependence most on weightlifting and without means other training For knowledge researcher did not know because whichever more influential "(weightlifting or Albulayomterc) in the development of the ability explosive, and the belief of the researcher scientific research being and a way to get to the scientific facts so Artaú researcher of the study preference use weightlifting exercises or Albulayomterc in developing explosive power to the muscles of the two men hostile to (100 m) free for youth because of their great importance in the achievement in this event The research aims to: preparation exercises with weights and Albulayomterc to hostile (100 m) youth belonging to club Mahaweel sports, presumably researcher method training (Albulayomterc) is better than training method with weights in the development of the ability explosive to hostile (100 m) of young people, the same search One was players arena and field runners (100 m) youth who belong to the Mahaweel Sports Club’s (18) player, and the sample was divided into three groups as used first group weightlifting exercises, and the second exercises Albulayomterc, and the third used exercises trainer approach. After a series of actions the researcher concluded the following:ØCan rely on exercises (weightlifting - and Albulayomterc), as in the development of effective methods (explosive power of the two men), for the same search. To hostile (100 m) youth.ØThe exercises (Albulayomterc) have a big advantage in the development of explosive power to the muscles of the two men, for the same search. To hostile (100 m) youth .